Single-cell profiling of peanut-responsive T cells in patients with peanut allergy reveals heterogeneous effector T H 2 subsets - Chiang, David; Chen, Xintong; Jones, Stacie M; Wood, Robert A; Sicherer, Scott H; Burks, A Wesley; Leung, Donald Y M; Agashe, Charuta; Grishin, Alexander; Dawson, Peter; Davidson, Wendy F; Newman, Leah; et al. (Journal of allergy and clinical immunology, 2018)
The contribution of phenotypic variation of peanut-specific T cells to clinical allergy or tolerance to peanut is not well understood. Our objective was to comprehensively phenotype peanut-specific T cells in the peripheral blood of subjects with and without peanut allergy (PA). We obtained samples from patients with PA, including a cohort undergoing baseline peanut challenges for an immunotherapy trial (Consortium of Food Allergy Research [CoFAR] 6). Subjects were confirmed as having PA, or if they passed a 1-g peanut challenge, they were termed high-threshold subjects. Healthy control (HC) subjects were also recruited. Peanut-responsive T cells were identified based on CD154 expression after 6 to 18 hours of stimulation with peanut extract. Cells were analyzed by using flow cytometry and single-cell RNA sequencing. Patients with PA had tissue- and follicle-homing peanut-responsive CD4 T cells with a heterogeneous pattern of T 2 differentiation, whereas control subjects had undetectable T-cell responses to peanut. The PA group had a delayed and IL-2-dependent upregulation of CD154 on cells expressing regulatory T (Treg) cell markers, which was absent in HC or high-threshold subjects. Depletion of Treg cells enhanced cytokine production in HC subjects and patients with PA in vitro, but cytokines associated with highly differentiated T 2 cells were more resistant to Treg cell suppression in patients with PA. Analysis of gene expression by means of single-cell RNA sequencing identified T cells with highly correlated expression of IL4, IL5, IL9, IL13, and the IL-25 receptor IL17RB. These results demonstrate the presence of highly differentiated T 2 cells producing T 2-associated cytokines with functions beyond IgE class-switching in patients with PA. A multifunctional T 2 response was more evident than a Treg cell deficit among peanut-responsive T cells.